Acute shortening and subsequent lengthening of the radius and ulna for the treatment of an infected nonunion in a dog - Rahal, S. C. [UNESP]; Volpi, R. S. [UNESP]; Vulcano, L. C. [UNESP]; Ciani, R. B. [UNESP] (My University, 2001)
A 3-year-old, male crossbred dog with osteomyelitis of the radius and ulna was treated using Ilizarov's method. Two centimeters of infected bone was resected, then acute bone shortening and subsequent lengthening of a healthy bone site were performed. The infection was eradicated, but a residual leg-lenght discrepancy was present.